Eternal moment : selected poems - Weores, Sandor 1913-1989 (Corvina, 1988)
The unique poetic world of Sandor Weores has fascinated readers in Hungary ever since he began to publish poems in 1928, at the Mozartian age of fifteen. Today he is considered one of the greatest poets in his language and one of the major European poets of the century - 'a towering poet,' as Ted Hughes described him. In this, the first extensive English selection of his work, Weores' phenomenal range and inventiveness are mirrored in vigorous translations by British and American poets, chiefly Edwin Morgan and William Jay Smith, who also both write about their understanding and experience of Weores' poetry. The selection is drawn from all phases of his work and suggests its complex diversity, from lyrics to satires, sonnets to poems in prose and concrete poems, epigrams to the long poems which he calls 'symphonies'. Translations are also contributed by Alan Dixon, Daniel Hoffman, Hugh Maxton and George Szirtes, while Miklos Vajda's introduction sets Weores' life and work in its changing social and cultural context. What emerges is a portrait of a poet remarkable for the wealth of styles and forms that he commands, for the fertility of his imagination and the breadth of his sympathies.